Waste to Energy Conversion Technology - Rasheed, Ahmed Kareem; Ibrahim, Mohammed Khalil; Atiya, Jumah Barjes; Mohammed, Mohaimin Saleh (American Journal of Botany and Bioengineering, 2025)
With rapid urbanization and industrialization, the accumulation of municipal, agricultural, and industrial waste has emerged as a significant environmental and energy challenge worldwide. Although various waste management practices exist, the efficient conversion of waste into usable energy remains underutilized due to technological, economic, and regulatory barriers. This study explores diverse waste-to-energy (WtE) conversion technologies, including incineration, gasification, pyrolysis, and anaerobic digestion, emphasizing their thermochemical and biochemical mechanisms. Using a comprehensive analytical approach, the paper assesses the technical feasibility, environmental impact, and economic viability of each method across different waste streams. The findings underscore the transformative potential of integrating advanced WtE technologies into national energy and waste strategies. This integration not only reduces landfill dependency and greenhouse gas emissions but also contributes to sustainable energy production and circular economy initiatives, especially in developing nations.